Acute Delta Hepatitis in Italy spanning three decades (1991–2019): Evidence for the effectiveness of the hepatitis B vaccination campaign. Issue 1 (7th October 2021) - Stroffolini, Tommaso; Morisco, Filomena; Ferrigno, Luigina; Pontillo, Giuseppina; Iantosca, Giuseppina; Cossiga, Valentina; Crateri, Simonetta; Tosti, Maria Elena
Abstract: Updated incidence data of acute Delta virus hepatitis (HDV) are lacking worldwide. Our aim was to evaluate incidence of and risk factors for acute HDV in Italy after the introduction of the compulsory vaccination against hepatitis B virus (HBV) in 1991. Data were obtained from the National Surveillance System of acute viral hepatitis (SEIEVA). Independent predictors of HDV were assessed by logistic‐regression analysis. The incidence of acute HDV per 1‐million population declined from 3.2 cases in 1987 to 0.04 in 2019, parallel to that of acute HBV per 100, 000 from 10.0 to 0.39 cases during the same period. The median age of cases increased from 27 years in the decade 1991–1999 to 44 years in the decade 2010–2019 ( p  < .001). Over the same period, the male/female ratio decreased from 3.8 to 2.1, the proportion of coinfections increased from 55% to 75% ( p  = .003) and that of HBsAg positive acute hepatitis tested for by IgM anti‐HDV linearly decreased from 50.1% to 34.1% ( p  < .001). People born abroad accounted for 24.6% of cases in 2004–2010 and 32.1% in 2011–2019. In the period 2010–2019, risky sexual behaviour (O.R. 4.2; 95%CI: 1.4–12.8) was the sole independent predictor of acute HDV; conversely intravenous drug use was no longer associated (O.R. 1.25; 95%CI: 0.15–10.22) with this. In conclusion, HBV vaccination was an effective measure to control acute HDV. Intravenous drug use is no longer an efficient mode of HDV spread. Testing for IgM‐anti HDV is a grey area requiring alert. Acute HDV in foreigners should be monitored in the years to come.